Eligibility of Dapagliflozin and Empagliflozin in a Real-World Heart Failure Population - Erik Håkansson; Helena Norberg; Sara Själander; Krister Lindmark (Cardiovascular Therapeutics)
Aims. This study is aimed at investigating the eligibility in a real-world heart failure population for the DAPA-HF (testing dapagliflozin) and EMPEROR-reduced (testing empagliflozin) trials, comparing the eligible real-world patients to trial participants and to characterize the noneligible patients. Methods. Medical records of all heart failure patients who had a diagnosis of heart failure from the Heart Centre or Department of Internal Medicine at Umeå University Hospital were reviewed. Results. 2433 of the hospital’s uptake population of 150 000 had a diagnosis of heart failure. 681 patients had left ventricle ejection fraction≤40%, and of these 352 (52%) and 268 (39%) patients met eligibility criteria for DAPA-HF and EMPEROR-reduced, respectively. Comparing eligible patients in our population with the DAPA-HF- and EMPEROR-reduced trial populations, we found that eligible real-world patients were older (79.0 vs. 66.2 years and 80.3 vs. 67.2 years, respectively), had worse renal function (eGFR 54.4 vs. 66.0 ml/min/1.73m2 and 49.5 vs. 61.8 ml/min/1.73m2, respectively), higher prevalence of atrial fibrillation (56.0% vs. 36.1% and 53.0% vs. 35.6%, respectively), and lower prevalence of diabetes mellitus (21.0% vs. 41.8% and 26.1% vs. 49.8%, respectively). The main reasons for ineligibility were low NT-proBNP or low eGFR. Noneligible patients differed according to reason for ineligibility, where patients with low NT-proBNP were generally younger and healthier, and patients with low eGFR were older and had more comorbidities. Conclusions. 39-52% of patients with heart failure and reduced ejection fraction in this real-world heart failure population were eligible for SGLT2-inhibitor treatment, corresponding to 11-14% of all heart failure patients. Compared to trial participants, eligible real-world patients were significantly older with worse renal function, more atrial fibrillation, and less diabetes mellitus. Trial entry criteria exclude comparatively young and healthy patients, as well as comparatively old patients with more comorbid conditions.